The UK’s referendum on EU membership of June 2016: how expectations of Brexit’s impact affected the outcome - Fisher, S; Renwick, A (Springer, 2018)
The UK voted by a narrow margin to leave the European Union in a referendum on 23 June 2016. This article examines why this was the result and brings out comparative implications. Building on previous findings that expectations about the impact of Brexit were central to voters’ decisions, we seek to improve understanding of how these expectations mattered. On average across a range of issues, our analysis suggests that Leave would have won if voters had expected things to stay much the same following Brexit. A big exception is immigration, for which “no change” is associated with Remain voting. But there was a clear expectation that immigration would fall after Brexit (as most voters wanted). That consideration strengthened the Leave vote, and did so sufficiently to overwhelm a more important but less widely and strongly held expectation that the economy would suffer. We also find that those who were uncertain about where Brexit might lead were more likely to back the status quo. This supports a posited tendency towards status quo bias in referendum voting, notwithstanding a widespread belief that this bias failed to materialize in the Brexit vote. Our methods and findings have valuable implications for comparative research.